2022
DOI: 10.1089/mdr.2020.0417
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequencing of a Citrobacter freundii Strain Isolated from the Hospital Environment: An Extremely Multiresistant NDM-1 and VIM-48 Coproducing Isolate

Abstract: Citrobacter freundii has acquired resistance to several antimicrobial drugs, including last-resort antibiotics affecting, therefore, clinical efficacy and causing high rates of mortality. In this study, we investigate the whole genome sequence of a carbapenem-resistant C. freundii strain isolated from the hospital environment in Tunisia. A total of 210 samples were taken using sterile swabs, from inanimate surfaces, medical devices, and care staff, during the period extended between March and April 2019. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…population is dominated by diverse STs with different characteristics and varied geographical distributions. ST22 and ST98 isolates with different carbapenemases (VIMs, KPC-2, NDM-1, OXA-48) were previously reported from Spain ( 21 , 22 ), Tunisia ( 23 ) and Germany ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…population is dominated by diverse STs with different characteristics and varied geographical distributions. ST22 and ST98 isolates with different carbapenemases (VIMs, KPC-2, NDM-1, OXA-48) were previously reported from Spain ( 21 , 22 ), Tunisia ( 23 ) and Germany ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Isolates harboring IncX3 plasmids are found in many countries around the world ( Figure 1 ), including China (CHN), South Korea (KOR), Switzerland (SWI), Czech (CZE), Italy (ITA), Australia (AUS), India (IND), Japan (JPN), Netherlands (NED), Brazil (BRA), Germany (GER), South Africa (ZAF), Myanmar (MYA), the United States (USA), France (FRA), Ghana (GHA), Spain (ESP), the United Arab Emirates (AE), Cambodia (CAM), Canada (CAN), Denmark (DEN), Egypt (EGY), Kuwait (KUW), Pakistan (PAK), Poland (POL), Portugal (POR), the United Kingdom (UK), Oman (OMA), Vietnam (VIE), Algeria (DZA), Angola (AGO), Burkina Faso (BFA), Chad (TCD), Nigeria (NGA), Tanzania (TZA; Supplementary material ), Tunisia (TUN; Dziri et al, 2022 ), Lebanon (LBN; Dagher et al, 2018 ), Ethiopia (ETH; Legese et al, 2022 ), Croatia (HRV; Petrosillo et al, 2016 ), Turkey (TUR; Peirano et al, 2022 ), and Gabon (GAB; Moussounda et al, 2017 ). Among them, China is the country with the most reported IncX3 plasmids.…”
Section: Distribution Of Incx3 Plasmids In Region Source and Hostmentioning
confidence: 99%
“…Bacteremia caused by Citrobacter spp. can be nosocomial or community-acquired (Doran, 1999;Lai et al, 2010;Dziri et al, 2022). Also, infections caused by Citrobacter spp.…”
Section: Bacteremiamentioning
confidence: 99%
“…Studies on carbapenemresistant Citrobacter spp. found that the Inc family of plasmids was the primary group that carries genes for carbapenem resistance (Cao et al, 2021;Dziri et al, 2022;Ju et al, 2022); and was one of the main reasons for the rapid dissemination of carbapenem-resistant Citrobacter spp. around the world.…”
Section: Antibiotic Resistancementioning
confidence: 99%